Activated pulverized coal membrane for effective solar-driven interfacial evaporation and desalination. (16th January 2023) - Wang, Jiacheng; Wang, Ruilin; Geng, Yang; Li, Yanjin; Li, Jianbo; Qiu, Jing; Li, Meng
Highlights: The coal was used for the development of a low-cost and energy efficient water desalination system. The pulverized coal membrane exhibited a water evaporation rate as 0.94 kg m −2 h −1 (0.265 mg cm −2 ). A portable solar evaporation device is designed based on the APC membrane. Abstract: Given the current crisis of freshwater resources facing humankind, solar evaporation has attracted a lot of interest as a promising means of seawater desalination. Although numerous photothermal materials have been investigated in previous literature, there remain challenges to explore economically viable materials with high efficiency of photothermal conversion. In this paper, an eco-friendly and low-cost activated pulverized coal-based (APC) membrane is developed based on an industrial raw material, Zhundong coal, through KOH activation. A considerable water evaporation rate as high as 0.94 kg m −2 h −1 was achieved with a minimal loading capacity of 0.265 mg cm −2 . In addition, the mechanism of the enhancement effect of activation on photothermal properties of the pulverized coal is identified by experiment and characterization. Moreover, APC shows superiority in terms of sewage treatment and excellent economic potential in seawater desalination. Based on this, a portable solar evaporation device is designed for the exploration of the practical application. The present work is an innovative attempt to employ pulverized coal as a solar–thermal material, which extends the possible applications of coal.